Incorporating Asian music characteristics: a variation on the theme music history from a hermeneutic perspective - Jahnichen, Gisa (Universiti Pendidikan Sultan Idris, 2013)
Reading the introduction into the International Conference John Cage 101 held in August 2013 in Tanjung Malim, Malaysia, the following two sentences caught my attention: “Cage was an early proponent of the need for Western music to incorporate Asian music characteristics. He studied Zen and I Ching, both philosophies having a powerful impact on his music, writings and art.”1 This paper examines the essence of this statement that seems to commend openness and at the same time points towards a globally dominating perception of musical intellectuality rooted in the West, a place that John Cage to some extent intended to leave. He studied what many studied before him, the I Ching [Yì Jīng]. By doing so, how much could he contribute to the world of composition? Methodologically, this paper will focus on the hermeneutic perspective in discussing Asian music characteristics that are incorporated into contemporary music compositions. Taking further some teaching texts on John Cage to illustrate various viewpoints on what music history may encompass if seen as an open system of events and doings that are positioned according to actual needs, the paper serves to summarise a few findings from recent observations in discussing musical and historical terminology in and outside Asia.